Formation, topography and reactivity ofCandida antarcticalipase B immobilized on silicon surface - Miletic Nemanja, Nemanja; Fahriansyah, null; Nguyen, Le-Thu T.; Loos, Katja (Biocatalysis and Biotransformation, 2010)
Candida antarctica lipase B (CaLB) was immobilized on silicon wafers previously modified with aminopropyltriethoxysilane (APTES) and activated with glutaraldehyde (GLA). The various steps of immobilization were characterized using transmission FTIR, AFM, contact angle measurements and XPS. Furthermore, the formation of APTES films during the initial immobilization step was additionally analyzed by ellipsometry and an ‘ island ’ monolayer film formation was revealed. When the concentration of APTES was increased, the amount of immobilized lipase also increased. On the other hand, while the activity of immobilized enzyme in lipase-catalyzed transesterification of 6,8-difluoro-4-methylumbelliferyl octanoate initially increased, showing the highest value when 0.00050% w/v APTES solution was used for the initial immobilization step, it subsequently decreased. Comparison of enzyme activity and surface filling results indicate that there has to be multilayer formation in the enzyme layer, as revealed by AFM images and determination of enzyme loading. Published